Rectum cancer: The effects of perioperative outcomes of patients as long-term prognostic factor (Annals of Medical Research, 2021)
Aim: The majority of studies about adjacent segment disease (ASD) in the literature concern adult patients who were operated on because of degenerative process-related diseases, such as lumbar instability or lumbar stenosis.Material and Methods: We retrospectively reviewed cases of AIS surgically treated in our institution between 2012 and 2015. Patients with an increase in the amount of disc degeneration at adjacent segment (AS) (the ASD group) were compared with those with no increase in degeneration at AS (the non-ASD group).Results:ASD was observed postoperatively in 24 patients (57.1%), and 18 patients (42.9%) had no increase in disc degeneration at the latest follow-up.The mean follow-up was 13 to 34 months, with an average of 22±7.1 months and the lowest instrumented vertebra for 10 of the patients was L2, and the other 32 patients had L3. The rate of ASD in patients with fusion at T4-L3 was significantly higher than for the other instrumentation levels (p 0.05). All 24 patients in the ASD group had L3 as the lowest instrumented vertebra (LIV) (p 0.05).Conclusion: We believe that ASD is present even in short-term follow-up in patients who undergo long-segment fusion at a young age due to AIS and leaving as many mobile segments as possible will protect from ASD.